Role of sodium pyruvate in maintaining the survival and cytotoxicity of Staphylococcus aureus under high glucose conditions - Chen, Ti; Xu, Huan; Yao, Xiaoyan; Luo, Zhen (Frontiers in Microbiology, 2023)
Glucose is a crucial carbon source for the growth of Staphylococcus aureus, but an excess of glucose is detrimental and even leads to cell death. Pyruvate, the central metabolite of glycolysis, has been shown to have anti-inflammatory and antioxidant properties. This study aimed to investigate the protective effect of pyruvate on S. aureus under high glucose conditions. Sodium pyruvate greatly increased the cytotoxicity of S. aureus strain BAA-1717 to human erythrocytes and neutrophils in vitro. However, the cytotoxicity and survival of S. aureus were significantly reduced by high glucose, which was restored to normal levels by the addition of sodium pyruvate. The expression of hlg and lukS in S. aureus was higher in the LB-GP cultures than that in LB-G cultures, but there was no significant difference in cytotoxicity between LB-GP and LB-G cultures. Furthermore, the hemolytic activity of S. aureus supernatants could be inhibited by the cell-free culture medium (CFCM) of LB-G cultures, suggesting that high levels of extracellular proteases were presence in the CFCM of LB-G cultures, resulting in degradation of the hemolytic factors. The expression of sarA, which negatively regulates extracellular protease secretion, was higher in LB-GP cultures than that in LB-G cultures. Additionally, sodium pyruvate increased acetate production in S. aureus, which helps maintain cell viability under acidic environment. In conclusion, pyruvate plays an important role in the survival and cytotoxicity of S. aureus under high glucose conditions. This finding may aid in the development of effective treatments for diabetic foot infections.